Analisis Kinerja U-Turn pada Ruas Jalan Perak Timur dan Perak Barat Kota Surabaya - Wahyu Dimas Nur Mahendra; Nurani Hartatik; Laily Endah Fatmawati (Pusat riset dan Inovasi Nasional, 2024)
The growth in the number of vehicles in Surabaya has led to increased traffic congestion, particularly on the Perak Timur–Perak Barat road section, which serves as a major distribution route to the port and industrial areas. Problems arise at U-Turn points, where vehicle accumulation hampers traffic flow. This study analyzes traffic volume, travel time, queue length, and queue ratio at two U-Turn points on this section. The method used was a field survey with direct observation of vehicle volume every 15 minutes, vehicle classification, and queue length. Traffic volume was calculated using the Passenger Car Equivalent (PCE) factor based on the 1997 MKJI standards. The study results show that at Point 1, east–west direction, the highest queue ratio occurred on Tuesday from 11:00 to 12:00 (p = 4.84), while the lowest was on Sunday from 06:00 to 07:00 (p = 0.21). At Point 2, west–east direction, the highest queue ratio occurred on Tuesday from 08:00 to 09:00 (p = 6.18), and the lowest from 06:00 to 07:00 (p = 0.41). These findings indicate that during peak hours, traffic congestion increases (p > 1), causing long queues, particularly in the west–east direction in the morning. The performance of the U-Turn on the Perak Timur–Perak Barat road section needs improvement, with recommendations such as temporarily closing U-Turns during high volumes, providing alternative U-Turn lanes, and adding signs to minimize the potential for vehicle conflicts.